An Empirical Investigation of Electronic Health Record Adoption among Youth in Bangladesh (Bangladesh Journal of Medical Science, 2026)
Technological advancement has revolutionized the healthcare industry. Electronic Health Records (EHRs), being a prominent technological innovation, significantly changed the healthcare delivery system, offering various advantages to both healthcare providers and patients. Understanding the significance of EHR, this study integrates the Technology Acceptance Model with the IS success Model to investigate the factors shaping the perception of users towards EHR and its subsequent adoption. Data gathered from tertiary students through a survey and analyzed using PLS-SEM. Findings reveal that attitude toward EHR is significantly influenced by perceived usefulness, system quality, perceived cost, and perceived trust. Attitude, in turn, impacts EHR use intention. Theoretically, this study integrates the IS Success model with TAM and extends the model with perceived cost and perceived trust, enhancing existing literature on EHR adoption. Practically, this study provides insights to healthcare providers, system designers, and policymakers in advancing EHR adoption in developing country context.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 732-741